ANALISIS KONSEP TAQWA DALAM AL-QURAN: Studi Terhadap Ayat-Ayat yang Menyebutkan Taqwa - Fadillah, Ivan Fahmi (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
Taqwa is a central concept in Islam that describes a person's awareness, obedience, and piety to Allah. This concept is consistently mentioned in the Quran, providing guidance for Muslims to develop a deeper relationship with God and achieve spiritual success in life. Although piety is the center of attention in Islam, in-depth analysis of this concept in the Qur'an is still limited. Therefore, this research aims to study the concept of piety in the Quran and analyze the verses that contain it. This research uses the method of analyzing the Al-Quran text with a qualitative approach. The data is obtained from the verses of the Quran that specifically contain the word "taqwa" or its derivation. Content analysis techniques are used to explore the meaning of piety in the verses and understand the context. The results of the analysis are compared with classic and contemporary interpretations of the Qur'an to enrich understanding. The results of this research reveal that the concept of piety in the Quran involves elements such as obedience, awareness of God, avoidance of sinful acts, and efforts to fulfill His commands. Verses containing piety also associate this concept with spiritual and moral success. Context analysis reveals that piety is often associated with attitudes and actions that reflect submission to God and wisdom in daily life.